Soil microbial communities and soil quality drive Arabica coffee yield in pine-coffee agroforestry under varying management intensities - KARUNIAWAN PUJI WICAKSONO; PARAMYTA NILA PERMANASARI; AKBAR SAITAMA; EKO WIDARYANTO; CAHYO PRAYOGO; OKTAVIA RAHAYU ADIANINGSIH; ERNI SOFIA MURTINI; HAGUS TARNO (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Wicaksono KP, Permanasari PN, Saitama A, Widaryanto E, Prayogo C, Adianingsih OR, Murtini ES, Tarno H. 2026. Soil microbial communities and soil quality drive Arabica coffee yield in pine-coffee agroforestry under varying management intensities. Biodiversitas 27 (2): d270240. https://doi.org/10.13057/biodiv/d270240. Pine-coffee agroforestry systems provide important ecological and economic benefits; however, the effects of management intensity on soil quality, microbial communities, and coffee productivity remain poorly understood. This study evaluated the effects of varying management intensities in a pine-coffee agroforestry system, focusing on soil quality, microbial populations, and coffee productivity and quality. Field observations and laboratory analyses were conducted to assess canopy cover, light intensity, litter accumulation, soil bulk density, particle density, porosity, infiltration rate, total nitrogen, organic carbon, and populations of cellulolytic bacteria, fungi, Nitrobacter, and Nitrosomonas. Coffee productivity and fruit quality attributes were also evaluated. The results showed that higher management intensities, specifically best management practices (BMP), positively enhanced soil physical and chemical properties, thereby directly improving coffee yield and quality. The result revealed that BMP management effectively reduced soil bulk density and increased porosity and infiltration rates, creating an optimal environment for coffee plant growth. BMP can offer soil media with good physical characteristics and high nutrient content. However, MC management can provide a more favorable ecosystem for the growth of soil microbial populations. The more stable abiotic factors of the ecosystem under non-intensive management can support the development of microorganisms through succession. It was also observed that BMP practices led to larger berry sizes, heavier bean weights, and higher sugar content in coffee beans, which are critical quality indicators. The study demonstrates that management intensity strongly influences the interactions among soil quality, microbial communities, and coffee performance in pine-coffee agroforestry systems. Moderate to intensive management can improve productivity, but balanced practices are required to maintain soil microbial diversity and long-term ecosystem sustainability.